Microphysical processes under different hourly rainfall intensities in super typhoon Rammasun - Xue, Yidi; Cui, Xiaopeng (Frontiers in Earth Science, 2023)
High-resolution numerical simulation data of super typhoon Rammasun simulated by the Weather Research and Forecasting (WRF) Model was used to study the cloud microphysical processes under different hourly rainfall intensities. The grid points in the gale circle were categorized into four types (0-5, 5-20, 20-50, 50- mm) based on hourly rainfall. The results showed that on the eve of the first landfall, extremely hourly heavy precipitation (50- mm type) was significantly enhanced compared to other types. The vertical movement was significantly reduced to the middle and lower troposphere which was very conducive to the relative movement and interaction of hydrometeors with the enhancement of the collision processes. The rainfall in the 5-20 and 20-50 mm types both mostly accounted for about 40% of the total rainfall in the gale circle, while that of the 0-5 and 50- mm types were generally smaller than the former two. As the rainfall intensity increased, the absolute conversion rates of all major cloud microphysical processes had shown increasing trends, especially the non-uniformity of Cnd (the condensation of water vapor to cloud water), Pracw (the accretion of cloud water by rain) and Dgacw (the accretion of cloud water by graupel). The relative contribution of Pgmlt (the melting of graupel) increased slightly and then decreased significantly from the 20-50 mm type (36.28%) to the 50- mm type (25.06%), while that of Pracw had significantly increased especially from the 20-50 mm type (41.77%) to the 50- mm type (50.97%), which was related to the upward motion characteristics.